Analysis of Phase Velocity of Love Waves in Rigid and Soft Mountain Surfaces: Exponential Law Model. (19th May 2021) - Bharti, Uma; Vaishnav, Pramod Kumar; Abo-Dahab, S.M.; Bouslimi, Jamel; Mahmoud, K.H.
Abstract : Irregularity may occur on the earth's surface in the form of mountains due to the imperfection of the earth's crust. To explore the influence of horizontally polarized shear waves on mountains, we considered the fluid-saturated porous medium (superficial layer) over an orthotropic semi-infinite medium with rigid (Model-I) and soft (Model-II) mountain surfaces for wave propagation. The mountain surface is defined mathematically as a periodic function of the time domain. The physical interpretation of materials' structure has been explained in rectangular Cartesian coordinate system originated at the contact interface of layer and half-space. The displacement of the mountains has been derived by solving energy equations analytically. The influence of rigid and soft mountain surfaces on the phase velocity of shear waves has been demonstrated graphically (we used MATLAB software for graphical representations).